Liberalism, Post-liberalism and the Fact-Value Divide - Rashkover, Randi (Modern theology, 2017)
Jewish and Christian thought of the modern and contemporary period is frequently described as either liberal or post-liberal. In lieu of this widely accepted categorization, this essay narrates developments in modern and contemporary Jewish and Christian thought in wake of the impact of the fact-value dichotomy on theological and ethical discourse. This essay demonstrates the negative ramifications of this logical distinction on Jewish and Christian thought and shows how these negative repercussions can stimulate an immanent critique of this logic and a new paradigm in Jewish and Christian thinking.